2021
DOI: 10.14710/jkli.20.2.97-103
|View full text |Cite
|
Sign up to set email alerts
|

Risiko Gangguan Kesehatan Masyarakat Akibat Pajanan PM10 di Kota Padang

Abstract: Latar belakang: Pencemaran udara merupakan salah satu permasalahan kesehatan masyarakat yang mempunyai dampak serius pada kesehatan manusia dan kualitas lingkungan. Salah satu polutan udara yang dapat menyebabkan masalah kesehatan adalah partikel debu/ Particullate Matter (PM10). Kegiatan penambangan tanah liat di Gunung Sarik merupakan yang terbesar di Kota Padang. Proses pengangkutan tanah liat ke perusahaan, menimbulkan dampak terhadap masyarakat dan lingkungan sekitarnya. Penelitian bertujuan menganalisis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
(9 reference statements)
0
2
0
1
Order By: Relevance
“…In contrast to particulate 10, PM2.5 values tend to be higher in weeks 1-16, or from January to April. Just like particulate 10, particulate 2.5 also comes from motor vehicle combustion emissions and dusty road pollution, especially unpaved roads (Nur et al, 2021). Particulate 10 can harm the heart, infect the respiratory tract, interfere with bone growth in toddlers, and interfere with visibility (Armninarahmah & Kurniawan, 2020).…”
Section: Particulate 25 (Pm25)mentioning
confidence: 99%
“…In contrast to particulate 10, PM2.5 values tend to be higher in weeks 1-16, or from January to April. Just like particulate 10, particulate 2.5 also comes from motor vehicle combustion emissions and dusty road pollution, especially unpaved roads (Nur et al, 2021). Particulate 10 can harm the heart, infect the respiratory tract, interfere with bone growth in toddlers, and interfere with visibility (Armninarahmah & Kurniawan, 2020).…”
Section: Particulate 25 (Pm25)mentioning
confidence: 99%
“…Risiko dan efek gangguan kesehatan kana semakin tinggi, bila pekerja berada pada lingkungan tercemar dalam waktu lama dan sering. (16,17) Sebagian besar responden tidak mengkonsumsi rokok yaitu sebesar 68.8%. Merokok dapat menyebabkan perubahan struktur dan fungsi saluran pernafasan dan jaringan paru.…”
Section: Mendesainunclassified
“…This is supported by previous research which found that higher concentrations, longer durations, and more frequent exposure to PM 10 would increase the possibility of health risks. These results are also influenced by body weight, where the heavier a person is, the smaller the intake will be, and the lower the possibility of health risks (25).…”
Section: Health Risk Of Pm 10mentioning
confidence: 99%